Fostering Bilingual Creativity in English Poetry Classroom: A Postcolonial Creative Writing Strategy - Winda Setia Sari; Anna Tambunan; Citra Anggia Putri; Juli Rachmadani Hasibuan (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
The study accentuates bilingual creativity as the pedagogical intervention of postcolonial creative writing strategy in poetry class through the writing of haiku and short poems. Twenty-five students in their freshmen year at the English Department were engaged in reading a culturally local text (Sumatra-Javanese ethnic poetry to compose poetry from a post-colonial perspective). The workshop's five phases exploring, inciting inspirations, drafting, editing, and peer feedback provided the student, as a novice writer, with the benefit of familiarizing themselves with character, theme, and cultural issues; developing a cognitive process to negotiate different meanings in their first and second languages; and exploring creativity to write their own poetry in the second language. The scripts written in English are the product of poetry classes, which reveal students' localized knowledge and cultural literacy. The works reflect the participants’ cultural identity, even though English is the dominant language showcased in the almost fifty poems composed by the novice writers. The existence of local languages points to the development of their bilingual creativity; students in the poetry classroom are not only able to handle the meaning in the first and second languages, but also to promote their local culture to the global world.